Design of BDS-3 integrity monitoring and preliminary analysis of its performance. Issue 4 (15th February 2020) - Cao, Yueling; Chen, Jinping; Hu, Xiaogong; He, Feng; Bian, Lang; Wang, Wei; Wu, Bin; Yu, Yang; Wang, Jingyuan; Tian, Qiuning
Abstract: With the improvement in the service accuracy and expansion of the application scope of satellite navigation systems, users now have high demands for system integrity that are directly related to navigation safety. As a crucial index to measure the reliability of satellite navigation systems, integrity is the ability of the system to send an alarm when an abnormity occurs. The new-generation Beidou Navigation Satellite System (BDS-3) prioritized the upgrading of system integrity as an important objective in system construction. Because the system provides both basic navigation and satellite-based augmentation system (SBAS) services by the operational control system, BDS-3 adopts an integrated integrity monitoring and processing strategy that applies satellite autonomous integrity monitoring and ground-based integrity monitoring for both the basic navigation service and SBAS navigation service. BDS-3 also uses an improved and refined integrity parameter system to provide slow, fast and real-time integrity parameters for basic navigation, and provide SBAS-provided integrity information messages in accordance with Radio Technical Commission for Aeronautics (RTCA) specification and dual frequency, multi-constellation (DFMC) specification to support the SBAS signal frequency, single constellation operation and DFMC operation respectively. The performance of BDS-3 system integrity monitoring is preliminarily verified during on-orbit testing in different states, including normal operation, satellite clock failure and satellite ephemeris failure. The results show that satellite autonomous integrity monitoring, ground-based integrity monitoring and satellite-based augmentation all correctly work within the system. Satellite autonomous integrity monitoring can detect satellite clock failure but not satellite orbit failure. However, ground-based integrity monitoring can detect both. Moreover, the satellite-based augmentation integrity system monitors the differential range error after satellite ephemeris and clock error corrections based on user requirements. Compared to the near minute-level time-to-alert capability of ground-based integrity monitoring, satellite autonomous integrity monitoring reduces the system alert time to less than 4 s. With a combined satellite-ground monitoring strategy and the implementation of different monitoring technologies, the BDS-3 integrity of service has been considerably improved.